2019
DOI: 10.3390/toxins11020124
|View full text |Cite
|
Sign up to set email alerts
|

Function and Role of ATP-Binding Cassette Transporters as Receptors for 3D-Cry Toxins

Abstract: When ABC transporter family C2 (ABCC2) and ABC transporter family B1 (ABCB1) were heterologously expressed in non-susceptible cultured cells, the cells swelled in response to Cry1A and Cry3 toxins, respectively. Consistent with the notion that 3D-Cry toxins form cation-permeable pores, Bombyx mori ABCC2 (BmABCC2) facilitated cation-permeable pore formation by Cry1A when expressed in Xenopus oocytes. Furthermore, BmABCC2 had a high binding affinity (KD) to Cry1Aa of 3.1 × 10−10 M. These findings suggest that AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 95 publications
(202 reference statements)
2
43
0
Order By: Relevance
“…Using heterologous expression in Sf9 cells, ABCB1 was found to be a functional Cry3Aa receptor [19]. In comparison, an H. armigera strain with 6000-fold resistance to Cry2Ab [15] had a mutation in ABC subfamily A member 2 (HaABCA2), suggesting that ABCA2 is linked to Cry2Ab resistance [20]. This was confirmed using CRISPR/Cas9-mediated genome editing, leading to the conclusion that HaABCA2 determines the susceptibility of H. armigera to Cry2Aa and Cry2Ab [21].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Using heterologous expression in Sf9 cells, ABCB1 was found to be a functional Cry3Aa receptor [19]. In comparison, an H. armigera strain with 6000-fold resistance to Cry2Ab [15] had a mutation in ABC subfamily A member 2 (HaABCA2), suggesting that ABCA2 is linked to Cry2Ab resistance [20]. This was confirmed using CRISPR/Cas9-mediated genome editing, leading to the conclusion that HaABCA2 determines the susceptibility of H. armigera to Cry2Aa and Cry2Ab [21].…”
Section: Introductionmentioning
confidence: 81%
“…ATP-binding cassette (ABC) transporters, a class of transmembrane proteins, are found widely in organisms and are involved in Bt toxin activities [14]. Many studies seeking to identify functional receptors of target Cry toxins have focused on ABC transporters [15]. When BmABCC2 was expressed in S. frugiperda (Sf9) cells and Drosophila tissues that were originally insensitive, they became sensitive to Cry1 toxins, and when BmABCC2 was expressed in Xenopus oocytes the Cry toxins made pores in the membrane and cations flowed into the cells through these pores [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The most common and most potent mechanism of insect resistance to Bt toxins is disruption of toxin binding to larval midgut receptors, particularly cadherins and ATP-binding cassette (ABC) transporter proteins [17][18][19]. Resistance to crystalline (Cry) toxins of Bt in the Cry1, Cry2 or Cry3 families is associated with ABC transporter proteins in some lab-selected strains and field-selected populations of at least nine insect species [19][20][21][22][23][24][25][26][27]. In addition to studies implicating several ABC transporter proteins in resistance to Cry toxins, extensive evidence indicates many members of the superfamily of ABC transporter proteins protect cells by excreting xenobiotics, including ABC transporters that confer resistance to drugs and chemotherapy agents in humans and resistance to insecticides other than Bt in arthropods [20,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that the alteration of the membrane receptors is a common mechanism conferring high levels of resistance to Cry proteins (25-27). In the case of Cry1 proteins, an important body of literature identifies the main receptors altered in association with resistance, including aminopeptidase N, ABC transporters, cadherins and membrane alkaline phosphatases (28,29). In contrast, three candidate receptors have been proposed for Vip3A proteins, including the Spodoptera spp.…”
Section: Discussionmentioning
confidence: 99%